2016
DOI: 10.1186/s13063-016-1607-7
|View full text |Cite
|
Sign up to set email alerts
|

Neurofeedback training for alcohol dependence versus treatment as usual: study protocol for a randomized controlled trial

Abstract: BackgroundReal-time functional magnetic resonance imaging (rtfMRI) is used for neurofeedback training (NFT). Preliminary results suggest that it can help patients to control their symptoms. This study uses rtfMRI NFT for relapse prevention in alcohol dependence.Methods/designParticipants are alcohol-dependent patients who have completed a detoxification programme within the past 6 months and have remained abstinent. Potential participants are screened for eligibility, and those who are eligible are randomly as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…At some point in intervention development, the comparison of neurofeedback, either as a stand-alone or add-on intervention, to TAU is desirable (14). This design may be particularly useful in scenarios where TAU is widely available and can reveal whether the neurofeedback component is likely to have a clinically significant benefit over available treatments.…”
Section: No-training Controlmentioning
confidence: 99%
“…At some point in intervention development, the comparison of neurofeedback, either as a stand-alone or add-on intervention, to TAU is desirable (14). This design may be particularly useful in scenarios where TAU is widely available and can reveal whether the neurofeedback component is likely to have a clinically significant benefit over available treatments.…”
Section: No-training Controlmentioning
confidence: 99%
“…These additional publishing formats include preregistration, where researchers document their methodology with a timestamp on a public platform such as the Open Science Framework before data acquisition starts (e.g., Mehler et al, 2017). An alternative approach is to publish trial protocols in dedicated journals, which may be undertaken in parallel to data acquisition (e.g., Cox et al, 2016). Moreover, the recently introduced publishing format Registered Reports includes an initial peer-review stage that can grant authors acceptance in principle for their work independent of the statistical outcome.…”
Section: The Potential Of Fnirs For Neurofeedback Research -Future DImentioning
confidence: 99%
“…Depending on the study design and assessments, the experimental group may engage in a number of neurofeedback runs. For example, in Cox et al (Cox et al, 2016), the experimental group engaged in six neurofeedback sessions across 4 months while the control group attended four behavioural assessment sessions.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It was also shown that obese subjects' regulation ability during an fMRI based neurofeedback paradigm was higher compared to lean subjects (Frank et al, 2012). FMRI neurofeedback training for alcohol dependence has also been implemented (Cox et al, 2016). FMRI neurofeedback intervention can also be implemented in other neurological disorders that have been associated with dysfunctional eating habits in order to improve diet choice and eating behaviours.…”
Section: Other Eating Related Conditions and Behavioursmentioning
confidence: 99%